Farming Technology and Allocative Efficiency of Rice Production Factors in Kulon Progo Regency - Zuhriyyah Hasna Nur Fatimah; Waluyati, Lestari Rahayu; Utami, Arini Wahyu (HABITAT, 2024)
The regency of Kulon Progo, located in the western part of Yogyakarta Special Region, owns the lowest ratio of paddy fields relative to arable land, i.e., 0.27%, compared to other regencies in the region. Effective management of paddy farming technology is crucial to enhance productivity. This research aims to describe the management of rice farming technology and to analyze the allocative efficiency of rice production factors in Kulon Progo. The study employs cross-sectional data collected through observations and surveys using an open-ended questionnaire. The sampling method used is proportional stratified random sampling, with a total of 105 respondents, of which 55 from Panjatan Sub-district and 50 from Sentolo Sub-district. Data analysis methods include quantitative descriptive, multiple linear regression with the Cobb-Douglas production function, and calculation of allocative efficiency index (Ki) tested with the one-sample Wilcoxon test. The findings show that the majority of farmers use superior Ciherang seed varieties, insecticides for pest control, and adopt the rice cultivation method known as "jajar legowo". Moreover, a significant number of farmers have not yet adopted combine harvesters due to landscape unsuitability. Key production factors affecting rice output include land area, seed quantity, fertilizer application, farming experience, hybrid variety adoption, technical irrigation use, and combine harvester utilization. Allocative efficiency analysis reveals non-efficient land allocation, suggesting a need for land-use reduction. Meanwhile, seeds and fertilizers use are inefficient, warranting more allocations of these inputs.